Comparative Genomics of All Three Campylobacter sputorum Biovars and a Novel Cattle-Associated C. sputorum Clade. (19th June 2017) - Miller, William G.; Yee, Emma; Chapman, Mary H.; Bono, James L.
Abstract: Campylobacter sputorum is a nonthermotolerant campylobacter that is primarily isolated from food animals such as cattle and sheep. C. sputorum is also infrequently associated with human illness. Based on catalase and urease activity, three biovars are currently recognized within C. sputorum : bv. sputorum (catalase negative, urease negative), bv. fecalis (catalase positive, urease negative), and bv. paraureolyticus (catalase negative, urease positive). A multi-locus sequence typing (MLST) method was recently constructed for C. sputorum. MLST typing of several cattle-associated C. sputorum isolates suggested that they are members of a divergent C. sputorum clade. Although catalase positive, and thus technically bv. fecalis, the taxonomic position of these strains could not be determined solely by MLST. To further characterize C. sputorum, the genomes of four strains, representing all three biovars and the divergent clade, were sequenced to completion. Here we present a comparative genomic analysis of the four C. sputorum genomes. This analysis indicates that the three biovars and the cattle-associated strains are highly related at the genome level with similarities in gene content. Furthermore, the four genomes are strongly syntenic with one or two minor inversions. However, substantial differences in gene content were observed among the three biovars. Finally, although the strain representing the cattle-associated isolates was shown to be C. sputorum, it is possible that this strain is a member of a novel C. sputorum subspecies; thus, these cattle-associated strains may form a second taxon within C. sputorum .